Surface Properties and Potential Immunomodulatory Effects of Candidate Probiotic Lactobacilli for Gastrointestinal Applications - Rachael T. Duche; Jaspreet Kaur; Anamika Singh; Vikas Sangwan; Manvesh Kumar Sihag; Tochukwu N. T. Nwagu; Lewis I. Ezeogu; Harsh Panwar (Advanced Gut & Microbiome Research)
Conclusion: The indigenous lactobacilli (15ST2, 3BM3, and KN3) strains effectively adhered to intestinal cell surface and thereby have shown their potential to modulate the production of proinflammatory cytokines at both transcription and translation levels, when introduced alongside pathogens or established before bacterial infection.